STUDENTS’ DIFFICULTIES IN CHANGING PASSIVE VOICE IN INTERROGATIVE FORM - Adawiyah, Robiatul; ., Gusnadi; Sofyan, Deddy (ENGLISH JOURNAL, 2019)
The paper entitled "Students’ Difficulties in Changing Passive Voice in Interrogative Form” is written to analyze the students’ difficulties and the causes that make them difficult to change passive voice in interrogative form. The research was conducted to the third semester students of English Education Study Program, Faculty of Teacher Training and Educational Sciences, Pakuan University. The writer applied descriptive method and the data were gained from documentation, questionnaire and interview. All instruments are given to 28 students who became the respondents. In order to validate the data, the interview to the lecturers are also done. Based on the data, the writer finds out four types of students’ difficulties; they are difficulty in changing the position of subject and object, difficulty in determining appropiate auxiliary verb used, difficulty in determining which sentence can be changed into passive and difficulty in deciding the past participle. The causes also are found of two factors are internal factors such as first, students’ motivation; second, students’ intelligence and aptitude; at the last, students’ personality and learning style. Besides, external factors such as the material, the facility and atmosphere, as well as the lecturer’s explanation. The most factor that causes students’ difficulties are students’ motivation (internal factor) and lecturer’s explanation (external factor). As suggestions, students must increase their motivation especially internal motivation, basic skills in English grammar especially tenses then more pay attetion to the lecturer’s explanation and always ask the lecturer to minimize the difficulties.